Vanishing β-function for Grosse-Wulkenhaar model in a magnetic field - Ben Geloun, Joseph; Gurǎu, Rǎzvan; Rivasseau, Vincent (Physics letters, 2009)
We prove that the β-function of the Grosse-Wulkenhaar model including a magnetic field vanishes at all order of perturbations. We compute the renormalization group flow of the relevant dynamic parameters and find a non-Gaussian infrared fixed point. Some consequences of these results are discussed.
Available online 16 December 2008
Gesehen am 28.09.2022